2018
DOI: 10.1016/j.cell.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Convergence of Pathway-Specific Enzyme Expression Stoichiometry

Abstract: Coexpression of proteins in response to pathway-inducing signals is the founding paradigm of gene regulation. However, it remains unexplored whether the relative abundance of co-regulated proteins requires precise tuning. Here, we present large-scale analyses of protein stoichiometry and corresponding regulatory strategies for 21 pathways and 67-224 operons in divergent bacteria separated by 0.6-2 billion years. Using end-enriched RNA-sequencing (Rend-seq) with single-nucleotide resolution, we found that many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
225
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(261 citation statements)
references
References 86 publications
13
225
1
Order By: Relevance
“…Furthermore, the quantitative proteomic analysis 54 also showed that apart from an overall increase in mitochondrial protein mass, the mitochondrial proteome remains remarkably constant, even in a major metabolic adaptation, which is in accordance with the recent results of pathway-specific enzyme expression stoichiometry 48 . In other words, different genes participating in the similar related biological pathway are evolutionarily up-or down-regulated as a whole.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the quantitative proteomic analysis 54 also showed that apart from an overall increase in mitochondrial protein mass, the mitochondrial proteome remains remarkably constant, even in a major metabolic adaptation, which is in accordance with the recent results of pathway-specific enzyme expression stoichiometry 48 . In other words, different genes participating in the similar related biological pathway are evolutionarily up-or down-regulated as a whole.…”
Section: Discussionsupporting
confidence: 84%
“…Intriguingly, the results show that genes related to mitochondrial activities (marked by an asterisk) are suffered from a much stronger selection on mRNA secondary structure. Unlike just a few domesticated genes found in familiar species, such as yeast (e.g., AGT1 37 , a specific allele correlating with affinity for maltotriose), dog (e.g., AMY2B 46 , high copy number of this gene in dogs to exploit a starch-rich diet) and rice (e.g., SD1 47 , a null allele of which is known as a "green revolution gene"), adaptive alleles resulting from the effect of mRNA secondary structure are widespread among the genome, and they are commonly clustered in disparate biological pathways to guarantee the relative abundance of coregulated proteins (expression stoichiometry 48 ). This finding was never documented in yeast 37,45,49,50 or even other domesticated species (e.g., livestock 51 , pets 46,52 , and crops 47,53 ) before.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that shERa-dependent alterations in mRNA levels may be buffered at the level of translation such that the amount of mRNA associated with polysomes is unaltered despite changes in corresponding mRNA levels. Translational buffering has been described in the context of transcript-dosage compensation where it acts to maintain protein levels similar between different bacterial (Lalanne et al, 2018) and yeast species (Artieri & Fraser, 2014;McManus et al, 2014) and humans (Cenik et al, 2015). It has also been reported that gene dosage effects caused by aneuploidy may be compensated at the level of translation in a cell type-specific context (Zhang & Presgraves, 2017) and that translational buffering may reduce transcriptional "noise" caused by acute stimulation of cells with growth factors (Tebaldi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The secondary initiation hypothesis suggests that intrinsic terminators will be associated with nearby antisense 35 initiation ( Figure 5A). In E. coli, active intrinsic termination sites confirmed by Rend-seq data (Lalanne et al, 2018) were sometimes (in ~20% of cases) accompanied by nearby (within 500 bp) RNA 5´ ends on the opposite strand indicating highly significant (> 12 standard deviations above the mean; see Methods) antisense initiation ( Figure 5B, C, and D). These latter peaks were significantly more frequent near terminators than farther from them, indicating that the positions 40 of sense terminators and antisense initiation were correlated ( Figure S6A).…”
Section: Secondary Initiation Of Antisense Transcripts In Vivomentioning
confidence: 87%
“…The forgoing experiments demonstrate that secondary initiation occurs in vitro with 30 purified RNA polymerase and on a particular template DNA sequence but leave open the question of whether this phenomenon also occurs in living cells and on other template sequences. To investigate this, we used data from end-enriched RNA sequencing experiments that map the genomic positions of RNA 5´ and 3´ ends (Rend-seq; Lalanne et al, 2018). The secondary initiation hypothesis suggests that intrinsic terminators will be associated with nearby antisense 35 initiation ( Figure 5A).…”
Section: Secondary Initiation Of Antisense Transcripts In Vivomentioning
confidence: 99%